2010
DOI: 10.1063/1.3525097
|View full text |Cite
|
Sign up to set email alerts
|

Liquid filling in standard circular well microplates

Abstract: It is often assumed that droplets dispensed into standard microplate wells will automatically fill their bottoms. We show here by computational simulation and experimental verification that the ability to fill the well bottom is dependent on the surface wetting characteristics. The release of droplets at the center was also found to fill the well bottom better than droplet dispensation in contact with the well wall. Hydrophobic surfaces required higher liquid volumes to fill the well bottom; unlike the case wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Surface Evolver software was used to compute the predicted profile and size of inverted droplets. , It does this using an energy-minimization method that evolves a surface down the energy gradient. The assumption made in the computation was that an inverted static water drop on a surface should be identical to an immersed bubble on another surface with an opposing contact angle (as described in Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Surface Evolver software was used to compute the predicted profile and size of inverted droplets. , It does this using an energy-minimization method that evolves a surface down the energy gradient. The assumption made in the computation was that an inverted static water drop on a surface should be identical to an immersed bubble on another surface with an opposing contact angle (as described in Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…This method would be difficult to apply on small liquid volumes as it has been recently shown that it has a possibility of not filling the well bottom of standard microplates completely. 16 We show here that the shape of the meniscus in a circular capillary itself reveals the required information to determine the CA. Capillaries have been found to possess useful liquid filling characteristics that render them beneficial for use as alternative types of microplates with improved features.…”
Section: ' Introductionmentioning
confidence: 73%
“…Jika dibandingkan dengan microplate, biosensor ini memiliki beberapa keunggulan diantaranya harganya yang lebih terjangkau, pemakaiannya yang sederhana, dan analisisnya mudah bila menggunakan scanner karena bentuknya yang tipis. Menurut Lu dkk penggunaan microplate standar dengan diameter 6,5 mm, diperlukan volume cairan setidaknya 80 μL untuk menutup seluruh permukaan dasar microplate sedangkan pada penelitian ini menggunakan volume akhir yang lebih sedikit yaitu 20 μL [16]. Biosensor ini juga dapat digunakan secara berulang dengan mencuci biosensor kemudian mengganti lapisan alas dengan lapisan plastik yang baru.…”
Section: Karakterisasi Biosensorunclassified